Research on correlation between English writing self-efficacy and psychological anxiety of college students - Li, Bai (Frontiers in Psychology, 2022)
English writing is not only a cognitive process for college students, it is also influenced by factors related to the emotional or psychological level. With the continuous improvement of the quality of university education cultivation, the pressure faced by college students has increased significantly, which has also given rise to the general anxiety of college student groups. In order to investigate the correlation between college students’ English writing self-efficacy and English writing psychological anxiety, we conducted a questionnaire survey on 595 current college students who were not majoring in English at a university in China, and used SPSS 25.0 software to make an empirical analysis of the collected data. The results showed that college students’ English writing self-efficacy was at a moderate level and they lacked self-confidence in their English writing skills and tended to complete writing tasks; college students generally had a moderate level of psychological anxiety in English writing, among which avoidance behavior was the most significant; college students’ English writing self-efficacy was significantly negatively related to English writing psychological anxiety. English writing self-efficacy can reduce psychological anxiety by enhancing college students’ English writing motivation. Therefore, we suggest that we should set up English writing courses based on the process teaching method, change college students’ English writing psychology in teaching, set reasonable writing goals, mobilize their enthusiasm and motivation in English writing, reduce college students’ writing anxiety, and enhance their self-confidence in English writing.